Evaluation of the sensitivity of two recently developed STR multiplexes for the analysis of chimerism after haematopoietic stem cell transplantation. (18th May 2012) - Odriozola, A.; Riancho, J. A.; Colorado, M.; Zarrabeitia, M. T.
Summary Forensic‐oriented kits analysing short tandem repeat (STR) polymorphisms are widely used to determine the proportions of donor and recipient cells after haematopoietic stem cell transplantation. The sensitivity of this technology is crucial for the early detection of relapse and, in consequence, the adjustment of the treatment to enhance donor‐origin haematopoiesis in transplant recipients. The objective of this study was to compare the performance of two recently developed STR multiplex kits, AmpFℓSTR® Identifiler® Plus PCR Amplification Kit (Applied Biosystems) and Investigator™ IDplex® (Qiagen), in the analysis of chimerism. Fifteen STR loci were amplified with both kits in 26 peripheral blood samples of transplantated patients showing chimerism. Peak amplitude threshold, detection limit (%DL), per cent donor chimerism and efficacy of each multiplex and STR were determined, and the results with both kits were compared. The %DL and the estimated per cent donor chimerism were similar with both kits. On the other hand, Identifiler® Plus kit allowed chimerism identification only in 24 (92%) of the 26 cases with chimerism detected by using the Investigator™ IDplex® when only 'type 5' allelic constellations (i.e. without potential interference by stutter peaks) were taken into account. However, IDplex® efficacy was somewhat lower than that of Identifiler Plus when only the most informative loci (D2S1338, D21S11, D18S51 and FGA) were considered. Therefore, although each system had some particular advantages and disadvantages, overall both STR multiplexes showed similar performance in qualitative and quantitative chimerism analysis.